EMQs in Obstetrics and Gynaecology : Pt. 1, MCQs and Key Concepts - Akkad, Andrea; Habiba, Marwan; Konje, Justin; Taylor and Francis (Boca Raton, FL : Taylor and Francis, an imprint of CRC Press, 2017)
This work features a Foreword by David Taylor, Vice Dean, Leicester Medical School. "This book is the first to assist students with a new format of testing knowledge and clinical skills, i.e., the extended matching question. I am delighted my colleagues here in Leicester, where undergraduate education is given the very highest priority, have found the time and energy to write this book. This book comprehensively tests a whole range of obstetrics and gynaecology and I congratulate them for it." - David Taylor, in the Foreword. This revision aid in Obstetrics and Gynaecology is based on the Extended Matching Question format (EMQ) It contains over 200 patient vignettes arranged in topic areas covering a broad range of themes and degrees of difficulty. It provides test EMQs and detailed answers at the completion of each section. "EMQs in Obstetrics and Gynaecology" is an indispensable study and revision aid for undergraduate medical students preparing for in-course assessment in obstetrics and gynaecology as well as final exams. It also provides a vital review for specialist trainees in obstetrics and gynaecology preparing to take postgraduate exams.
How to answer emqs. Reading list. Normal pregnancy. Antenatal care and prenatal diagnosis. Common presentations in pregnancy. Complications of pregnancy. Therapeutics in pregnancy and puerperium. Labour, delivery and puerperium. Anatomy and sexual differentiation. Sexual health and family planning. Physiology and pathology of the menstrual cycle. Infertility. Common gynaecological presentations. Cancer in gynaecology. Screening and prevention. Operative gynaecology. Therapeutics in gynaecology. Ethics in obstetrics and gynaecology. Answers in obstetrics. Answers in gynaecology.
Includes bibliographical references and index.
Also available in print format.
Keywords: Gynecology -- Examinations -- Study guides; Obstetrics -- Examinations -- Study guides; Gynecology -- Examinations; Obstetrics -- Examinations; Obstetrics -- Examination Questions; Gynecology -- Examination Questions; Electronic books